Particle production as a function of charged-particle flattenicity in 𝑝⁢𝑝 collisions at √𝑠=13 TeV - Trubnikov, Vyacheslav; The ALICE collaboration (Physical Review D, 2025)
This paper reports the first measurement of the transverse momentum (p_T) spectra of primary charged pions, kaons, (anti)protons, and unidentified particles as a function of the charged-particle flattenicity in pp collisions at √s = 13 TeV. Flattenicity is a novel event shape observable that is measured in the pseudorapidity intervals covered by the V0 detector, 2.8 < η < 5.1 and -3.7 < η < -1.7. According to QCD-inspired phenomenological models, it shows sensitivity to multiparton interactions and is less affected by biases toward larger p_T due to local multiplicity fluctuations in the V0 acceptance than multiplicity. The analysis is performed in minimum-bias (MB) as well as in high-multiplicity events up to p_T = 20 GeV/c. The event selection requires at least one charged particle produced in the pseudorapidity interval |η| < 1. The measured p_T distributions, average p_T, kaon-to-pion and proton-to-pion particle ratios, presented in this paper, are compared to model calculations using PYTHIA 8 based on color strings and EPOS LHC. The modification of the p_T-spectral shapes in low-flattenicity events that have large event activity with respect to those measured in MB events develops a pronounced peak at intermediate p_T (2 < p_T < 8 GeV/c), and approaches the vicinity of unity at higher p_T. The results are qualitatively described by PYTHIA, and they show different behavior than those measured as a function of charged-particle multiplicity based on the V0M estimator.